PERANAN SISTEM INFORMASI AKUNTANSI SEBAGAI ALAT DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN PADA PT. BPR BUDISETIA - Fitri Sulistiyana; Hwihanus Hwihanus (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The accounting information system is needed by all parties, for internal and external to the company. The accounting information system will be one of the bases for making financial management decisions. Accounting information is obtained from the process of processing economic events which include collection, measurement, and processing. Accounting information can serve as a stimulus to achieve there is a problem with how actual performance records are presented Goals are set in budgets or notified to managers They fail to meet their production or profit targets Predetermined field studies are carried out by conducting on-site research at PT. BPR Budisetya. Literature research by collecting theoretical data Sourced from books, magazines and literature related to the issue discussed. Analysis of Accounting Information Systems management decisions are made through comparisons between theories to review the differences from the existing reality.